Association between stress, physical activity and body composition among adults in Terengganu - Wee, B.S.; Aryati, Ahmad; Karimah Fakhriah, Ismail (2018)
Psychological stress and obesity are emerging public health issues in adults globally. This study was conducted to determine the association between stress, physical activity and body composition among adults in Terengganu. Subjects comprised 259 adults aged 20 – 59 years from Kuala Nerus and Kuala Terengganu. Anthropometric measurement comprised weight, height and waist circumference; percentage of body fat by bioelectrical impedance analysis. . Asian BMI cut-off was used to categorize subjects into overweight/obese and non-overweight/obese groups. Asian waist circumference cut-off was used to categorize subjects into central obesity and noncentral obesity groups. Questionnaires were used to obtain data on socio-demographic characteristics. Malay version of DASS-21 and IPAQ were used to assess stress and physical activity level (PAL).Subjects were 86.9% Malays (n=225), 5.0% Chinese (n=13) and 8.1% Indians (n=21). Prevalence of stress was 16.6%. There was no significant association between stress and PAL with socio-demographic factors. There was also no significant association between PAL and BMI, waist circumference and percentage of body fat. Besides, no significant association was also found between stress and BMI, waist circumference and percentage of body fat. Nevertheless, BMI was significantly associated with gender (p<0.05), age (p<0.001) and ethnicity (p<0.05). Waist circumference was significantly associated with age (p<0.05) while percentage of body fat was significantly associated with gender (p<0.05). There was no significant association between stress and PAL. The finding of the study suggested there was no significant association between stress and physical activity with body composition. Assessment of stress, PAL and body composition are the initial health screenings to identify factors contributing to stress, physical inactivity and obesity. It should be conducted and maintained in long term to improve public health awareness among community.